Clinical Ethics Consultation in the Covid-19 Pandemic. Practical Challenges for Safety and Quality - Frewer, Andreas (Pandemics and Ethics. Development – Problems – Solutions, 2023)
The Corona pandemic poses a great challenge for medical and ethical counseling. Several areas of institutionalized expertise need to be distinguished here: At the level of care in hospitals, clinical ethics committees are required to deal with the problems and issues arising in the context of Covid treatment measures. The present article is dedicated to the practice of clinical ethics counseling and, based on cases that have arisen, sheds light on requirements in everyday life. Different forms of (in-)security in clinical practice in relation to the conduct of ethics counseling by telephone (2.) and video conference (3.) are considered, problems of relevant safety measures (4.) as well as “clinical side effects” of the pandemic (5.) are mentioned. In addition, the striving for quality assurance for clinical trials and research (6.) as well as the moral questions of the distribution of ventilation places and triage at the sickbed (7.) are to be discussed. Finally, summary considerations on security and insecurity under the conditions of the Covid-19 crisis and possible perspectives and necessary structural developments for the future (8.) are to be presented.
CRIS-Team Scopus Importer:2024-06-28